Research on the diagnosis of leakage hazards in a karst reservoir based on integrated electrical method and geological method - Yao, Jihua; Yang, Yuanli; Yang, Mingwei; Shen, Zhigao; He, Xiangjian; Chen, Xiang (Frontiers in Earth Science, 2025)
ObjectiveDue to the dual influence of karst features in the dam site area and the unique characteristics of the dam soil, leakage issues in the dam body and dam foundation of a certain reservoir have persisted, limiting the effectiveness of the reservoir. Despite multiple attempts at anti-leakage reinforcement, the leakage problems have not been completely resolved and have worsened in recent years. The detection and identification of karst reservoir leakage should be conducted more accurately and simply.MethodsThis paper integrates the use of High-density resistivity method and Frequency-Division and Electrical Resistivity Tomography method for the detection and identification of leakage in the karst reservoir, complemented by geological surveys and geological drilling for verification.ResultsThe leakage areas at the left and right ends of the dam base are caused by bypass seepage and contact leakage at the dam abutments. The perpetual water inflow in the sump wells at the middle and toe of the dam is mainly due to karst leakage in the dam foundation, leakage from the surface alluvial and depositional layers of the dam foundation, and contact leakage between the dam body and the dam foundation. Water seepage from within the culvert pipe body and its contact leakage with the dam body are the primary causes of scattered seepage on the fourth-level dam slope at the top of the power generation and irrigation culvert.ConclusionIntegrated electrical method and geological methods can accurately diagnose the leakage risks in karst reservoirs. This comprehensive detection method is easy to operate, highly accurate, and widely applicable for identifying leakage risks in similar earth-rock dam karst reservoirs.